2009
DOI: 10.1038/emboj.2009.168
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction between the COG complex and the SM protein, Sly1, is required for Golgi SNARE pairing

Abstract: The crucial roles of Sec1/Munc18 (SM)-like proteins in membrane fusion have been evidenced in genetic and biochemical studies. SM proteins interact directly with SNAREs and contribute to SNARE pairing by a yet unclear mechanism. Here, we show that the SM protein, Sly1, interacts directly with the conserved oligomeric Golgi (COG) tethering complex. The Sly1-COG interaction is mediated by the Cog4 subunit, which also interacts with Syntaxin 5 through a different binding site. We provide evidence that disruption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
124
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(136 citation statements)
references
References 68 publications
10
124
0
1
Order By: Relevance
“…Consistent with this view, we previously showed that the MTC Conserved Oligomeric Golgi (COG) positively regulates the assembly of Syntaxin5 (Stx5)-GS28-Ykt6-GS15 and Stx6-Stx16-Vti1a-VAMP4 SNARE complexes (Laufman et al, 2011;Laufman et al, 2009). These Golgi SNARE complexes and their corresponding SM (Sec1/Munc18) proteins Sly1 and Vps45, regulate intra-Golgi and endosome-to-TGN retrograde transport, respectively (Li et al, 2005;Mallard et al, 2002;Rahajeng et al, 2010;Xu et al, 2002).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Consistent with this view, we previously showed that the MTC Conserved Oligomeric Golgi (COG) positively regulates the assembly of Syntaxin5 (Stx5)-GS28-Ykt6-GS15 and Stx6-Stx16-Vti1a-VAMP4 SNARE complexes (Laufman et al, 2011;Laufman et al, 2009). These Golgi SNARE complexes and their corresponding SM (Sec1/Munc18) proteins Sly1 and Vps45, regulate intra-Golgi and endosome-to-TGN retrograde transport, respectively (Li et al, 2005;Mallard et al, 2002;Rahajeng et al, 2010;Xu et al, 2002).…”
Section: Introductionmentioning
confidence: 53%
“…These Golgi SNARE complexes and their corresponding SM (Sec1/Munc18) proteins Sly1 and Vps45, regulate intra-Golgi and endosome-to-TGN retrograde transport, respectively (Li et al, 2005;Mallard et al, 2002;Rahajeng et al, 2010;Xu et al, 2002). Although, the mechanisms by which COG regulates the assembly of these SNARE complexes have not been fully resolved, our previous studies suggest that the direct interactions between the Cog4 subunit of the complex, Sly1, and Stx5, and between the Cog6 subunit and Stx6, are essential for SNARE complex assembly in mammalian cells (Laufman et al, 2011;Laufman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the Sec1/Munc18 protein for HOPS, Vps33, is a stoichiometric member of the HOPS complex, whereas the exocyst binds transiently to its Sec1/Munc18 protein, Sec1, through Sec6 (73,74). Similarly, the COG complex, which is structurally related to exocysts, binds both the Sec1/Munc18 proteins Sly1 and Vps45 through its Cog4 subunit (75,76). These similar protein-protein interactions suggest that additional interactions and roles may be conserved across trafficking pathways and across species.…”
Section: Discussionmentioning
confidence: 99%
“…This region might, for example, interact directly with SNARE or SM proteins. It is intriguing in this regard that the region of lobe A where its four subunits interact has been shown to bind the SNARE protein Syntaxin-5 and the SM protein Sly1 (21,44,45). SNARE proteins assemble by forming membrane-bridging α-helical coiled-coil bundles, whereas SM proteins interact with and/or modulate formation of these bundles (46).…”
Section: Discussionmentioning
confidence: 99%